Engagement, Technology, and Language Tasks: Optimizing Student Learning - Joy Egbert (Cranmore Publishing, 2020)
The purpose of this paper is to share options for language instruction and present opportunities for language learning based on what the literature says about what makes an effective learning task. The paper focuses specifically on uses of technology to support learner engagement. The tasks and technologies presented are not intended to be prescriptive but rather to serve as models and idea generators for task design in a variety of English learning contexts. To meet the purpose, this paper presents a brief overview of conditions for language learning, and it then explains principles of task engagement. Applications and examples of technology uses that can support task engagement are included.